MODELING THE HYDRAULICAL BEHAVIOR OF A FISSURED-KARSTIC AQUIFER IN EXPLOITATION CONDITIONS - Debieche T.H.; Guglielmi Y.; Mudry J. (My University, 2002)
A 5-year daily measurement of the dynamic level in a borehole was plotted versus cumulative yield since the beginning of exploitation. Eighty percent of the experimental curve is explained by a linear function (h=aQc+h0) by intervals. Only floods, which follow heavy storms and non-pumping cannot be taken into account. The slopes of the straight lines are spread around two constant values of the slope: ar=+0.35x10-3mm-3, which characterizes the part which is controlled by recharge, and ap=-0.14x 10-3mm-3, which characterizes the draining part of the aquifer fractures. This linear fitting demonstrates that the borehole-aquifer system can be considered as an equivalent continuous medium, where the linear relationship between dynamic head and pumped yield are defined by the values of ar and ap. Thus the hydraulic behavior of the aquifer differs according to the pumping rate: equivalent continuous medium for a low rate, dual permeability for a high one. This work demonstrates that the long-term behavior of an exploited fissured aquifer can be described by a simple model, if the duration of the aquifer test is long enough (1-3 months). It also shows that the production phase must include repetitive head measurements in order to refine the exploitation yield and the management conditions.
Keywords: AQUIFER TEST; DISCONTINUOUS MEDIUM; KARST; EXPLOITATION BOREHOLE